1715. A Randomized, Double-Blind, Placebo-Controlled Multicenter Phase 2 Trial to Examine the Effects of DAS181 in Immunocompromised (IC) Patients With Parainfluenza Virus (PIV) Lower Respiratory Tract Infection (LRTI) on Supplemental Oxygen (SO). (26th November 2018) - Chemaly, Roy F; Moss, Ronald; Marty, Francisco M; Wolfe, Cameron R; Lawrence, Steven J; Dadwal, Sanjeet; Soave, Rosemary; Hwang, Jimmy; Hawley, Stephen; Routh, Rebecca; Ho, Jennifer; Wang, George; et al.
Abstract: Background: PIV infections are an important cause of morbidity and mortality in IC patients. DAS181, a sialidase fusion protein, has demonstrated activity in preclinical and clinical studies. Methods: Adult IC patients diagnosed with PIV LRTI on chest imaging and required SO ≥ 2 L/minute were randomized 2:1 (stratified by mechanical ventilation [MV] at baseline) to nebulized DAS181 (4.5 mg in 3.5 mL/day) or matching placebo for up to 10 days. The primary endpoint was the proportion of patients reaching clinical stability survival (CSS, defined as alive, resolution of SO requirement, and normalization of vital signs) by Day 45. Results: From 2014 to 2016, 110 patients were randomized and received study drug (74 DAS181 and 36 placebo). Median age was 57 years (range, 18–85). The majority were hematopoietic cell transplant (HCT) recipients (74), followed by hematological malignancy/solid tumor patients on chemotherapy (29), and lung transplant recipients (7). Day 45 CSS was achieved by 39.2% of DAS181-treated patients compared with 31.4% of placebo ( P = 0.29), while the proportion among non-MV patients was 45.0% vs. 31.0% (difference −14.0%, P = 0.15), respectively. Time to CSS in the non-MV stratum was shorter in DAS181-treated patients (figure). Median change in nasopharyngeal PIV viral load by Day 10 and median hospitalization days were −1.44 vs. −0.68 log10 ( P = 0.51) and 13.5 vs. 21 days ( P = 0.10) for DAS181 and placebo, respectively. Mean absolute increase from baseline FEV1% predicted was 16.82 for DAS181 vs. 2.02 for placebo ( P = 0.001). Post-hoc analysis on the probability to return to room air (RTRA) suggested that DAS181 reduced SO need in the non-MV stratum after Day 21 ( P = 0.09). HCT recipients within 360 days from transplant had a 40.8% treatment effect on RTRA at Day 28 ( P = 0.04) and 36.7% on mortality at Day 45 when compared with placebo ( P = 0.06). The rate of adverse events was similar in both treatment groups. Day 45 all-cause mortality was comparable in both groups (32.4% DAS181 vs. 31.4% placebo). Conclusion: DAS181 was well tolerated and showed a signal for clinical efficacy in IC patients with PIV LRTI. DAS181 was granted Breakthrough Therapy Designation for the treatment of PIV LRTI in IC patients and a phase 3 trial is being planned. Disclosures: R. F. Chemaly, Ansun Biopharma: Consultant and Investigator, Consulting fee and Research grant. R. Moss, Ansun Biopharma: Employee, Salary. F. M. Marty, Ansun Biopharma: Investigator, Research grant. C. R. Wolfe, Ansun Biopharma: Investigator, Research grant. S. J. Lawrence, Ansun Biopharma: Investigator, Research grant. S. Dadwal, Ansun Biopharma: Investigator, Research grant. R. Soave, Ansun Biopharma: Investigator, Research grant. J. Hwang, Ansun Biopharma: Employee, Salary. S. Hawley, Ansun Biopharma: Employee, Salary. R. Routh, Ansun Biopharma: Employee, Salary. J. Ho, Ansun Biopharma: Employee, Salary. G. Wang, Ansun Biopharma: Employee, Salary. N. Chang, Ansun Biopharma: Employee, Salary. M. Boeckh, Ansun Biopharma: Consultant and Investigator, Consulting fee and Research support.